2021
DOI: 10.1371/journal.pone.0247844
|View full text |Cite
|
Sign up to set email alerts
|

Rotational stability of modified toric intraocular lens

Abstract: We evaluated the rotational stability of a new toric intraocular lens (IOL), HOYA XY-1 toric IOL that is an improved version of HOYA 355 toric IOL, with longer overall length (13.0 mm vs. 12.5 mm), shortened unfolding time, and texture processing of the surface of haptics. Data from 193 eyes of 165 patients (76.4 ± 8.3 years old) with preoperative corneal astigmatism exceeding 0.75 diopters who had undergone phacoemulsification and toric IOL implantation were collected and analyzed. Corneal astigmatism, refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
(8 reference statements)
4
21
0
Order By: Relevance
“…Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4 , 9 , 10 , 12 , 17–19 confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5 , 9 , 18 , 20–24 the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25 , 26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°). 18 …”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4 , 9 , 10 , 12 , 17–19 confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5 , 9 , 18 , 20–24 the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25 , 26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°). 18 …”
Section: Discussionsupporting
confidence: 65%
“…These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5 , 9 , 18 , 20–24 the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25 , 26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°). 18 …”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Previous studies demonstrated that postoperative rotational stability varies across different model of toric IOLs 2 7 , indicating that the design, material, and surface finish of the IOL, especially haptics, should be among the important factors affecting postoperative rotational stability of toric IOLs. One study revealed that modification of the haptics of a toric IOL, by increasing overall length, reducing unfolding time, and introducing texture processing to the surface of haptics, significantly reduced postoperative axis misalignment 8 .…”
Section: Introductionmentioning
confidence: 99%